2022
DOI: 10.1002/jmv.28325
|View full text |Cite
|
Sign up to set email alerts
|

The effect of SARS‐CoV‐2 infection on cardiac function in post‐COVID‐19 survivors: A systematic review and meta‐analysis

Abstract: The longitudinal trajectories of cardiac structure and function following SARS‐CoV‐2 infection are unclear. Therefore, this meta‐analysis aims to elucidate the effect of SARS‐CoV‐2 infection on cardiac function in coronavirus disease 2019 (COVID‐19) survivors after recovery. PubMed/MEDLINE, CENTRAL, and EMBASE were systematically searched for articles published up to 1st August 2022. A systematic review and meta‐analysis were performed to calculate the pooled effects size and 95% confidence interval of each ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 76 publications
(323 reference statements)
1
40
0
Order By: Relevance
“…We conducted a study that included: a double CPET assessment, and a mental health Exclusion criteria: pulmonary condition (COPD, uncontrolled bronchial asthma, blood saturation <95%), cardiovascular disease (arrhythmia confirmed by ECG, ischemia of myocardium, QT prolongation confirmed by ECG, morphological heart abnormalities confirmed by echocardiography, uncontrolled hypertension >160/100 mmHg), [28] present mental condition, (4) an orthopedic condition that prevents EA to perform CPET, (5) deviations in CBC (leukocytosis >10,000•mm -3 , anemia with blood hemoglobin <10g•dL -1 ).…”
Section: 1general Study Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…We conducted a study that included: a double CPET assessment, and a mental health Exclusion criteria: pulmonary condition (COPD, uncontrolled bronchial asthma, blood saturation <95%), cardiovascular disease (arrhythmia confirmed by ECG, ischemia of myocardium, QT prolongation confirmed by ECG, morphological heart abnormalities confirmed by echocardiography, uncontrolled hypertension >160/100 mmHg), [28] present mental condition, (4) an orthopedic condition that prevents EA to perform CPET, (5) deviations in CBC (leukocytosis >10,000•mm -3 , anemia with blood hemoglobin <10g•dL -1 ).…”
Section: 1general Study Informationmentioning
confidence: 99%
“…[4]. COVID-19 infection has been shown to have an adverse effect on the heart function of patients who survived the infection [5]. A greater tendency to reduced left ventricular ejection fraction, end-diastolic volume, stroke volume was found.…”
Section: Introductionmentioning
confidence: 97%
“…studies have indicated the potential for individuals to experience long-term cardiovascular and cerebrovascular complications following recovery from severe COVID-19 infection. [3][4][5] Notably, the risk of stroke appears to be notably elevated in patients who have experienced severe COVID-19. 4,6 However, existing studies have certain limitations that warrant further exploration.…”
Section: Several Observational and Mendelian Randomization (Mr)mentioning
confidence: 99%
“…More than three years into the COVID‐19 pandemic, and at least 65 million people are believed to be living with long COVID (also known as post‐acute sequelae of COVID‐19 (PASC) as at January 2023 1 . According to the Centre for Disease Control, long COVID is defined as a post‐COVID‐19 condition in which there is new, evolving or persistent health issues occurring ≥4 weeks after SARS‐CoV‐2 infection 2 Emerging evidence reports that fatigue (27.4%), anosmia (25%), impaired lung diffusion capacity (24.6%), alopecia (10.2%), and dyspnoea (10.1%) are the most frequent symptoms and findings in COVID‐19 survivors 2 years after SARS‐CoV‐2 infection 3 …”
Section: Introductionmentioning
confidence: 99%
“…Long COVID symptoms have been demonstrated to have a crippling effect with significant impact on patient's quality of life 1 . Globally, labour force has struggled owing to a good number of long COVID patients that are yet to return to their original work and presently, there are no known effective pharmacological or non‐pharmacological interventions 1,3,9 . Though myriads of pathophysiological factors have been implicated including dysregulated immune response that results in some degree of tissue damage, 10 the exact cause of residual symptoms remains unclear 11 …”
Section: Introductionmentioning
confidence: 99%